2011
DOI: 10.1016/j.ajpath.2011.05.024
|View full text |Cite
|
Sign up to set email alerts
|

KSHV Regulation of Fibulin-2 in Kaposi's Sarcoma

Abstract: Kaposi's sarcoma is an angioproliferative tumor caused by Kaposi's sarcoma-associated herpesvirus (KSHV) infection of vascular endothelial cells. Fibulins, proteins that associate with extracellular matrix (ECM) proteins, may have both tumor-suppressive and oncogenic activities. We found that the expression of fibulin-2 protein and mRNA were decreased 50-fold and 26-fold, respectively, in 10-day KSHVinfected dermal microvascular endothelial cells (DMVEC). Using quantitative RT-PCR, we found a fivefold and 25-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Figure 6C shows a succinct list of the most regulated genes in LEC-219s identified by our RNA-seq approach. The host genes previously reported to be modulated in KSHV-infected endothelial cells are depicted in bold (72,(75)(76)(77)(78)(79). The full list of KSHV-regulated genes is available in Data Set S3 in the supplemental material.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6C shows a succinct list of the most regulated genes in LEC-219s identified by our RNA-seq approach. The host genes previously reported to be modulated in KSHV-infected endothelial cells are depicted in bold (72,(75)(76)(77)(78)(79). The full list of KSHV-regulated genes is available in Data Set S3 in the supplemental material.…”
Section: Resultsmentioning
confidence: 99%
“…Fibulin 1 disruptions cause synpolydactyly in humans, which is characterized by malformation of distal limbs due to bone fusion (12). Fibulin 2 is down-regulated in breast cancer, colorectal cancer, lung cancer, Kaposi's sarcoma, esophageal squamous cell carcinoma, nasopharyngeal carcinoma and childhood acute lymphoblastic leukemia (13)(14)(15)(16)(17). The down-regulation of fibulin 2 in these cancers is either due to methylation of its promoter, gene deletion, or simply down-regulation of the levels of protein (13,14).…”
mentioning
confidence: 99%
“…Angiogenesis is critical for the growth of solid tumors and some hematological malignancies . Studies have demonstrated that VEGF/VEGFR‐related pathways are the most relevant regulators of neoangiogenesis, vasculogenesis, and recruitment of endothelial progenitor cells . VEGF is expressed at an elevated level by KSHV‐infected endothelial cells and KS spindle cells and is a key mediator of angiogenesis and vascular permeability in KS lesions .…”
Section: Discussionmentioning
confidence: 99%